Funding Formula by Islamic Participate Possibility to Use as A Alternative of Credit Facilities - Shallof, Nori A, Dr. Anton Agus Setyawan, SE., M.Si, Dr. Agung Riyardi, M.Si (2014)
This study talks about the funding method by participation Islamic Bank and the possibility of applying it as an alternative to credit facilities. The study covered making participation activities in the practical life, the idea was implemented by changing the activity of the banks of credit facilities into Islamic participation according to syaria, funding by participation provides permanent work and successful investment within Islamic banks and acting along with the contribution of the Islamic bank in funding by participation and increasing the investment and national income reinforcement and national income reinforcement. An Islamic bank adopting funding by participation will have a successful impact in replacing the credit facilities in the trade banks where establishing Islamic banks. The fundamental problem that has plagued Bank Republic and all commercial banks in Libya, a deal beneficial usury by granting loans and advances to customers and here we seek participatory process Islamic alternative successful to solve the problem that has plagued the bank of the republic and all Libyan banks which usury Term funding HTP Islamic received acceptance excellent Republic by the bank as an alternative to a successful its investment.